MIRERC 059/2025: Tackling Psychological Barriers to Job Search and Employment in Kenya - Dr. Matthew White Ridley; Dr. Richard LeBeau; Dr. Ulrike Malmendier; Dr. Kate Orkin; Mr. Chazel Hakim; Ms. Anasuya Narasimhan; Mr. Dylan Reich; Ms. Emeldah Precious; Raphael Malenya; Isaac Obara; Mutwiri, Antony (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
Executive Summary Young jobseekers in developing countries often struggle to get on the career ladder. One reason could be that finding and then keeping a new job is psychologically challenging. The stress of rejection and uncertainty may discourage jobseekers from applying ‘enough’, and anxiety about work may affect performance in interviews or when starting work. Yet the economic benefits of. psychological interventions to help jobseekers cope with work- and job search-related anxiety have been little studied in developing countries. In Nairobi, Kenya we first aim to evaluate, in a randomized controlled trial (RCT), whether a psychological intervention, aimed at reducing fear of rejection and work-related anxiety, can improve job-finding rates, particularly for those who start less resilient to job-search stress. Second, we propose to study how the same psychological intervention affects downstream labour market outcomes- in particular, on-the-job performance. We will measure the productivity (performance) of some job seekers in simple tasks that they will do in our study office. Participants will be invited to our lab to complete 6-weeks of work, primarily revolving around data entry and a customer service training task with virtual customers. They will have additional opportunities to work in teams, present what they have learnt, and negotiate terms of pay. We will measure how they perform in each of these set-ups. Third, we will also measure how our intervention affects performance on a mock job-application, where we will collect participant CV , Cover Letter, and have them complete skill-assessments commonly used by employers. Participants will also complete a mock video interview. We will measure job application “performance” based on how a set of Kenya-based recruiters perceive participants’ application materials. Collectively, our study of the effects of these interventions will seek to evaluate the effect of alleviating psychological constraints, stemming from depression, anxiety and stress, at three distinct stages of an individual’s labour market activity (job search, individual work performance and work-in-teams). Our results will provide us with a rich picture of how labour markets can be used as a tool for poverty alleviation amongst those vulnerable.